The status and trends of type 2 diabetic osteoporosis research: a global bibliometric and visualization analysis over the past 20 years - Haiyan Hou; Liying Zhu (Frontiers in Clinical Diabetes and Healthcare)
BackgroundType 2 diabetic osteoporosis (T2DOP) has received considerable attention due to its accelerated bone deterioration and significantly increased fracture risk. Unlike classical osteoporosis, patients with T2DOP often exhibit a paradoxical pattern: they have normal or even elevated bone mineral density (BMD) in early stages despite deterioration in bone microarchitecture. This paradox highlights the clinical importance of identifying T2DOP as a distinct and critical subtype of secondary osteoporosis.MethodsWe conducted a bibliometric analysis of literature on T2DOP published over the past 20 Years(from 2001 to 2020), using data retrieved from the Web of Science Core Collection database. Bibliometric networks were visualized and analyzed using VOSviewer. Publication trends, geographic contributions, research hotspots, and keyword clusters were systematically examined.ResultsOver the past 20 Years, global research output on T2DOP steadily increased, with major contributions from North America, East Asia, and Western Europe. Identified research hotspots included risk prediction, biomarkers (e.g., advanced glycation end-products), complication management, population-specific characteristics (e.g., postmenopausal women), and therapeutic strategies (e.g., metformin). Notably, lifestyle intervention has recently emerged as an important new research direction.ConclusionsThis study provides the first comprehensive bibliometric analysis and visualization of global research trends and hotspots in T2DOP, highlighting critical insights for clinical practice, including the identification of at-risk populations, biomarker-guided risk assessment, and therapeutic optimization, which complements existing clinical meta-analyses. Future research efforts should emphasize multidisciplinary collaboration and validation of the long-term efficacy of lifestyle interventions. For clinical practice, integrating bone density evaluation with biomarker screening (e.g., osteocalcin) in diabetic patients could enhance early fracture prevention. Public health initiatives should prioritize lifestyle interventions in high-risk populations (e.g., postmenopausal women) to mitigate the growing burden of diabetic osteoporosis.